Local responsive branding for MSMEs: a culturally adaptive design framework based on Nusantara philosophy - Yazidiz Azmi Zain; Taufik Murtono; Ana Rosmiati; Danur Condro Guritno (Pascasarjana Institut Seni Indonesia Surakarta, 2025)
MSMEs often struggle to build consistent, authentic, and competitive brand identities, especially within culturally rich local contexts. The primary issue is the limitation of branding strategies that fail to adequately represent local identity and are less responsive to audience needs. This research addresses this gap by aiming to design and evaluate the application of the local responsive design (LRD) method on the culinary MSME OppaBay to strengthen its brand differentiation and competitiveness. The methodology employs a qualitative approach through observation, interviews with the business owner, and questionnaire-based evaluations involving design experts and partners/clients. The study introduces LRD as a novel framework integrating local aesthetic, linguistic, and cultural elements into MSME branding. The results demonstrate that LRD successfully produced a consistent visual identity, an authentic, culturally based narrative, and brand communication that is familiar and audience-relevant. Expert evaluation confirmed the design's suitability with principles of visual communication, aesthetics, and cultural branding. Concurrently, partners found the design practical, easy to implement, and supportive of improving professional image and consumer trust. The conclusion confirms that LRD provides both theoretical utility, enriching the study of local branding, and significant practical value for small business sustainability. Future research should focus on strengthening culture-based digital storytelling and measuring the relationship between cultural branding and consumer loyalty.